Analyzing 'Himawari No Yakusoku' in 'Stand by Me Doraemon' through film soundtrack and communication theories - Yefya Bako; Dandi Hafiddin; Feysya Salsabila Ramadhani (Universitas Pendidikan Indonesia, 2024)
This study examines the impact of the song